Effect of intercropping of maize and cowpea on the yield, land productivity and profitability of components crops in Bena- Tsemay Woreda, Southern Ethiopia - Biruk, G; Awoke, T; Anteneh, T (International Journal of Agricultural Research, Innovation and Technology, 2022)
Field experiment was carried out during the 2017-18 cropping season at Kako, Bena-Ttsemay woreda, South Omo zone, Southern Ethiopia to determine the effect of intercropping of maize and cowpea on the yield, land use efficiency and profitability of both crops. The experiment consisted of 4 treatments (sole maize, sole cowpea, one row maize to one row cowpea and one row maize to two-row cowpea) and laid in RCBD in four replications. Intercropping of one row maize to one row cowpea and one row maize to two-row cowpea, resulted in 55.8% and 27.9% greater land use efficiency than for either crop grown alone. The highest MAI was obtained by growing one row of maize to one row of cowpea (11563.17) followed by one row maize to two-rows of cowpea (6783.50).Based on the present finding, intercropping of one row maize and one row cowpea more economic advantage than the other crop combination or grown alone. Therefore, intercropping of one row maize to one row cowpea is an advantageous to farmers in the study area since it would provide additional crop yield with the same piece of land and more profitable related to cost benefit. Int. J. Agril. Res. Innov. Tech. 11(2): 147-150, Dec 2021